MEDIA PEMBELAJARAN ANIMASI TIGA DIMENSI UNTUK TATA CARA BERWUDHU DAN SHALAT BERBASIS VIRTUAL REALITY - Ramadhani; Feri Susilawati; Putri Raihana (Politeknik Aceh, 2019)
Prayer is one of the pillars of Islam that must be known and studied by all Muslims in this world. So far the procedure for ablution and prayer is learned using conventional methods, namely only by using books and oral as a learning guide. This has become one of the problems of Muslims, especially students who are less able to directly understand the procedures for ablution and prayer properly. In the current digital era, this problem can be overcome by creating a three-dimensional animation application in practicing the procedures for ablution and prayer. This application is based on Android using virtual reality. Virtual Reality is a technology used by users to interact with computer simulation environments based on both real objects and animations.